Совершенствование протокола направления пациентов на эндодонтическое лечение с использованием стоматологического микроскопа (LLC "Endo Press", 2020)
The authors present of data on the problems of use of a dental microscope in endodontic practice. Submitted questionnaire of a referral of patients to endodontic treatment.